VIOLENCE IN ROMANIAN SCHOOLS (PANGEEA, 2025)
Human violence is one of the most important themes of contemporary societies, being approached from different perspectives on different categories of population. Violence is an increasingly common phenomenon in contemporary society. Each approach to the subject has strengths and limitations, but to fully distinguish violence from other behaviors it is necessary to observe it from individual episodes to its occurrence in groups and society.
Keywords: human violence; victims; aggressors; gangs; bullying